2005
DOI: 10.1007/s00535-005-1576-1
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of BNIP3 by 5-aza-2′-deoxycytidine sensitizes pancreatic cancer cells to hypoxia-mediated cell death

Abstract: BNIP3 expression is silenced in some pancreatic cancer cells by the methylation of its CpG island. Demethylation of BNIP3, using a methyltransferase inhibitor, restores the gene's expression and induces hypoxia-mediated cell death. BNIP3 may thus be a useful target for new therapies aimed at treating pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 31 publications
4
41
0
1
Order By: Relevance
“…Okami et al detected hypermethylation of the BNIP3 promoter in most of the BNIP3-silenced pancreatic cancer cell lines examined, including AsPC-1, Miapaca-2 and PANC-1 and in eight of ten primary pancreatic cancer tissues (Okami et al, 2004). Abe et al (2005) showed that BNIP3 promoter methylation was strong in the Miapaca-2, PK-8, PK-9 and PK-59 cell lines but weak in PANC-1 and CFPAC-1. For our study, we selected AsPC-1, Miapaca-2, PK-1 and PANC-1 for further investigation of BNIP3 promoter methylation and regulation of expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Okami et al detected hypermethylation of the BNIP3 promoter in most of the BNIP3-silenced pancreatic cancer cell lines examined, including AsPC-1, Miapaca-2 and PANC-1 and in eight of ten primary pancreatic cancer tissues (Okami et al, 2004). Abe et al (2005) showed that BNIP3 promoter methylation was strong in the Miapaca-2, PK-8, PK-9 and PK-59 cell lines but weak in PANC-1 and CFPAC-1. For our study, we selected AsPC-1, Miapaca-2, PK-1 and PANC-1 for further investigation of BNIP3 promoter methylation and regulation of expression.…”
Section: Discussionmentioning
confidence: 99%
“…The promoter of BNIP3 is located within a CpG island and is methylated in most pancreatic cancer cell lines (Abe et al, 2005;Akada et al, 2005;Erkan et al, 2005). Restoration of BNIP3 expression by the methyltransferase inhibitor, 5-aza-2-deoxycytidine, leads to the death of pancreatic cancer cells in response to hypoxia.…”
Section: Introductionmentioning
confidence: 99%
“…BNIP3 is one factor that has been found to be required to mediate autophagic cell death in response to hypoxia through HIF1a activities (Daido et al, 2004;Tracy et al, 2007a;Azad et al, 2008). The loss of BNIP3 in pancreatic and colon tumours, either by hypermethylation or by transcriptional repression, is correlated with inhibition of cell death (Okami et al, 2004;Murai et al, 2005;Bacon et al, 2007;Mahon et al, 2007), whereas up-regulation of BNIP3 sensitizes pancreatic carcinoma cells to hypoxia-induced cell death (Abe et al, 2005). Aleman et al (2005) have shown that cell death resulting from SIM2s antisense treatment of colon cancer RKO cells was apoptotic, being largely dependent on the activities of caspases 9 and 10; however, mechanisms of autophagy have not been investigated.…”
Section: Sim2s Attenuates Hypoxic Induction Of Bnip3 Via Activities Wmentioning
confidence: 99%
“…It is activated by HIF during hypoxia and initiates programmed cell death through apoptosis or autophagy (Ray et al, 2000;Mellor and Harris, 2007). Epigenetic silencing of BNIP3 by promoter hypermethylation has been reported in several cancer types and contributes to resistance to hypoxia-induced cell death (Okami et al, 2004;Abe et al, 2005;Yan et al, 2006). The role of BNIP3 in colorectal cancer (CRC) is unknown, although 66% tumours show BNIP3 silencing by promoter hypermethylation Bacon et al, 2007).…”
mentioning
confidence: 99%